Fatores que influenciam o comportamento de citação de docentes-pesquisadores do campo da Cancerologia brasileira - Kátia de Oliveira Rodrigues (2017)
This research aims at analyzing the factors that influence the citation behavior of the docent-researchers of the postgraduate programs in the field of Brazilian Cancerology, in the period 2005-2015. The theoretical framework involves authors and conceptualizations of scientific communication, studies and citation analysis, as well as documents related to the field of Cancerology in Brazil. As for the methodological instruments, quantitative and qualitative techniques came into play. The corpus of the research is composed of six postgraduate programs in the field of Brazilian Cancerology, which offer Academic and PhD Masters: PPG-FAP; PPG-HCB; PPG-INCA; PPG-UFPA; PPG-USP and PPG-USP/RP. In the first stage of the research, following the quantitative model, the author applies a citation analysis onto the 6,057 productions of 245 docent-researchers listed in the Curriculum Lattes section "Complete articles published in journals", published in the period 2005-2015 and indexed on the Web of Science. It was decided at this stage to carry out a bibliometric study, from which the productions of the docent-researchers were characterized, as well as the citations present in these productions. In the second phase, following the qualitative model, the author interviews 15 of these 245 teacher-researchers, following a structured interview; then submits these interviews to content analysis, which allowed a better understanding of the citation behavior in the studied field, especially with respect to the factors that influence it. The results showed that the field of Brazilian Cancerology is a field in the process of consolidation. Of the six programs investigated, only PPG-INCA scored six in the Capes evaluation for the period 2013-2016. Regarding the citation behavior, there emerged the following patterns: predominance of citations in English; in multiple authorship; scientific article; recent productions; articles published in journals with Qualis/Capes A1, A2 and B1 in the evaluation of 2013-2016; and foreign authors. Based on the results of the qualitative stage, the factors influencing the citation behavior of Brazilian Cancerology researchers fall into two main categories: the conceptual-argumentative and the sociopolitical, inspired by the works of authors such as Erikson and Erlandson (2014), Silveira, Caregnato and Bufrem (2014), and Bourdieu (1983a, 1983b, 2004, 2014). The conceptual-argumentative order refers to those factors linked to the citing authors need to convey credibility to his statements in the scientific text, by citing other productions. The sociopolitical ones are associated with those tendencies that guide the citation behavior in the field, in order to allow the citing author to create alignment with authors already consecrated in the field, seeking recognition from their peers. In general influenced by both types of factors, the citation behavior is a more or less conscious choice made by the citing author, and, in order to be better understood, requires an understanding by the researcher of the field in which it is situated.